Comprehensive survey on effect of mobility over routing issues in wireless multimedia sensor networks. Issue 4 (7th November 2016) - Borawake-Satao, Rachana; Prasad, Rajesh
Abstract : Purpose: Wireless Multimedia Sensor Network (WMSN) is expected to be a key technology for future network. The multimodal information along with very low-cost availability of the camera sensor nodes is promoting the extensive use of audio, image and video in various real-time implementations. The purpose of this paper is to study various routing issues and the effect of mobility on existing solutions for the applications in future internet. Design/methodology/approach: This paper conducts a survey of the various methodologies for routing and the vital issues in the design of routing protocols for WMSN, and it also discusses about the effect of mobility on various routing methodologies of WMSN. WMSN ubiquitously performs data acquisition, processing and routing for scalar and multimedia data in a mobile environment. The routing protocols should be adaptive in nature and should have a dynamic approach to service effectively for future network. Many authors proposed the mobility of sink to improve lifetime of the network. This paper discusses some effective approaches for the network where not only the sink node but also some of the sensor nodes are mobile. Findings: During the survey, the performance and lifetime of the network are discussed, other parameters like delay, packet loss, energy consumption and simulators used for implementation are also discussed. Originality/value: The techniques in this paper represent a considerable solution for mobility issues in future internet applications.